2014
DOI: 10.1097/mej.0000000000000106
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of mortality in community-acquired pneumonia after implementing standardized care bundles in the emergency department

Abstract: This study demonstrated that implementation of standardized CAP care bundles in the ED is associated with a 21% relative risk reduction of in-hospital mortality. Standardization of diagnostic and therapeutic processes in the ED improves outcome of patients hospitalized for CAP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0
5

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 0 publications
0
13
0
5
Order By: Relevance
“…Georges et al [95] reported that a similar bundle including antibiotic therapy, fluids, and vasoactive agents was associated with a decrease in mortality from 43 % to 31 % in patients with severe CAP as defined by ICU admission in a single French centre. Hortmann et al [96] implemented a care bundle for all patients with CAP in a German ED. The bundle comprised checklists on history, clinical examination, investigations including lactate measurement and blood cultures, risk stratification according to CRB65, and treatment including antibiotic guidelines and fluid resuscitation.…”
Section: Methodsmentioning
confidence: 99%
“…Georges et al [95] reported that a similar bundle including antibiotic therapy, fluids, and vasoactive agents was associated with a decrease in mortality from 43 % to 31 % in patients with severe CAP as defined by ICU admission in a single French centre. Hortmann et al [96] implemented a care bundle for all patients with CAP in a German ED. The bundle comprised checklists on history, clinical examination, investigations including lactate measurement and blood cultures, risk stratification according to CRB65, and treatment including antibiotic guidelines and fluid resuscitation.…”
Section: Methodsmentioning
confidence: 99%
“…40 On the other hand, studies have shown that timely management with an intervention bundle significantly improves outcomes of severe CAP. [41][42][43][44][45][46] Therefore, recognition and management of severe CAP as medical emergency has been advocated to improve patient prognosis. 32 What do these data imply for initial risk stratification?…”
Section: Identification Of High-risk Patients In the Ed: The Concept mentioning
confidence: 99%
“…We have concluded that standardization of diagnostic and therapeutic processes in the ED is associated with improved outcome for patients hospitalized with CAP [1]. We have concluded that standardization of diagnostic and therapeutic processes in the ED is associated with improved outcome for patients hospitalized with CAP [1].…”
mentioning
confidence: 89%